The Role of Peroxiredoxins in Cancer Development - Pratik Thapa; Hong Jiang; Na Ding; Yanning Hao; Aziza Alshahrani; Qiou Wei (Biology, 2023)
Peroxiredoxins (Prxs) are antioxidant enzymes with ubiquitous expression in human tissues. Prxs are expressed in archaea, bacteria, and eukaryota, often in multiple isoforms. Because of their abundant expression in different cellular organelles and extraordinary sensitivity to H2O2, Prxs are among the first defenses against oxidative stress. Prxs undergo reversible oxidation to disulfides, and some family members perform chaperone or phospholipase functions upon further oxidation. Prxs are upregulated in cancer cells. Research has suggested that Prxs can function as tumor promoters in various cancers. The major objective of this review is to summarize novel findings regarding the roles of Prxs in common cancer types. Prxs have been shown to influence differentiation of inflammatory cells and fibroblasts, remodeling of extracellular matrix, and regulation of stemness. Since aggressive cancer cells have higher intracellular levels of ROS that they can utilize to proliferate and metastasize compared to normal cells, it is critical that we understand the regulation and functions of primary antioxidants such as Prxs. These small but mighty proteins could prove to be key for improving cancer therapeutics and patient survival.